Prognostic and predictive role of YKL-40 in anal squamous cell carcinoma: a serological and tissue-based analysis in a multicentric cohort - Gambella, Alessandro; Senetta, Rebecca; Falco, Enrico Costantino; Ricci, Alessia Andrea; Mangherini, Luca; Tampieri, Cristian; Fissore, Jessica; Orlando, Giulia; Manetta, Tilde; Mengozzi, Giulio; Mistrangelo, Massimiliano; Bertero, Luca; et al. (Frontiers in Medicine, 2024)
Introduction Anal squamous cell carcinoma (ASC) is a rare gastrointestinal malignancy showing an increased incidence over the past decades. YKL-40 is an immune modulator and pro-angiogenetic factor that showed a promising prognostic and predictive potential in several malignancies, but limited data are available for ASC. This study aims to provide an extensive evaluation of the prognostic and predictive role of YKL-40 in a multicenter cohort of ASC patients. Methods We retrospectively retrieved 72 consecutive cases of ASC diagnosed between February 2011 and March 2021. Both serum and tissue protein expression of YKL-40 were assessed, the latter in ASC tumor cells and peritumor immune cells. Results Increased YKL-40 serum levels at the time of diagnosis were associated with older age (p = 0.035), presence of cardiovascular/metabolic comorbidities (p = 0.007), and death for any cause (p = 0.011). In addition, high serum levels of YKL-40 were associated with a poor prognosis (HR: 2.82, 95% CI: 1.01–7.84; p = 0.047). Protein expression of YKL-40 in ASC tumor cells was significantly associated with low tumor grade (p = 0.031), while the increased expression in peritumor immune cells was associated with a worse response of patients to chemoradiotherapy (p = 0.007). However, YKL-40 protein expression in ASC tumor cells or peritumor immune cells did not significantly impact patient overall survival. Discussion In conclusion, YKL-40 resulted a relevant prognostic (serum level) and predictive (tissue protein expression in peritumor immune cells) biomarker and can considerably improve ASC patient clinical management.